(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article describes artistic projects inside prisons in the city of Campo Grande, state of Mato Grosso do Sul (MS), and examines the use of these projects as disciplinary devices of the school inside the prison environment. Using Foucault, the article addresses problems and tensions that emerge from discipline in the bodies of incarcerated subjects. Artistic practice plays a significant role in the process of building an identity for incarcerated people beyond the prison’s walls, but it is also used by the institution as tool for keeping incarcerated people occupied, without valuing them as artists who are capable of growth.